Expression of Prostate-Specific Membrane Antigen in Tumor-Associated Vasculature Predicts Poor Prognosis in Hepatocellular Carcinoma. Issue 5 (22nd May 2019) - Jiao, Dian; Li, Yu; Yang, Fa; Han, Donghui; Wu, Jieheng; Shi, Shengjia; Tian, Feng; Guo, Zhangyan; Xi, Wenjin; Li, Guodong; Zhao, Aizhi; Yang, An-Gang; et al.
Abstract : INTRODUCTION: Prostate-specific membrane antigen (PSMA) was originally found to be specifically expressed in normal prostate, and its expression was upregulated in almost all stages of prostate cancer. In recent years, PSMA was also found to be expressed in tumor-associated vasculature in many nonprostatic solid tumors. However, the expression pattern of PSMA in hepatocellular carcinoma (HCC) is not well studied. METHODS: In this study, we examined PSMA expression in 103 HCC tissues using immunohistochemical staining and analyzed the association between PSMA expression and other clinicopathological features and prognosis. RESULTS: Among the 103 cases, 27 cases (26%) showed PSMA expression in more than 50% of tumor-associated vasculature, 49 cases (48%) showed PSMA expression in less than 50% of vasculature, and 27 cases (26%) did not have detectable PSMA expression. Vascular PSMA expression was associated with several clinicopathological features, such as tumor stage, tumor differentiation, lymph node metastasis, and Ki-67 index. Furthermore, high vascular PSMA expression was also associated with poor prognosis in patients with HCC. Univariate and multivariate analyses showed that high vascular PSMA expression can be used as an independent prognostic marker for HCC. DISCUSSION: Our study provides the evidence that PSMA is specifically expressed in tumor-associated vasculature of HCC, and vascular PSMA expression may be used as a novel prognostic marker and a vascular therapeutic target for HCC.